2018
DOI: 10.1021/acs.macromol.7b02706
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Ion Transport in Polyether-Based Electrolytes for Lithium Batteries

Abstract: ABSTRACT:We report on the synthesis of poly(diethylene oxidealt-oxymethylene), P(2EO-MO), via cationic ring-opening polymerization of the cyclic ether monomer, 1,3,6-trioxocane. We use a combined experimental and computational approach to study ion transport in electrolytes comprising mixtures of P(2EO-MO) and lithium bis(trifluoromethanesulfonyl) imide (LiTFSI) salt. Mixtures of poly(ethylene oxide) (PEO) and LiTFSI are used as a baseline. The maximum ionic conductivities, σ, of P(2EO-MO) and PEO electrolytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
146
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(157 citation statements)
references
References 79 publications
11
146
0
Order By: Relevance
“…The product of the cation transference number, t+, and the total conductivity, σtotal, thus provides a measure of the cation conductivity. 27 A more precise definition of transference number depends on the method used for measurement.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The product of the cation transference number, t+, and the total conductivity, σtotal, thus provides a measure of the cation conductivity. 27 A more precise definition of transference number depends on the method used for measurement.…”
Section: Figurementioning
confidence: 99%
“…It is possible that this is due to solvation site connectivity, which has been shown to play a dominant role in mobility for lithiumpolyether systems. 27 Thus, there remains significant opportunity to identify chemistries alternative to PEO that exhibit higher ionic conductivities for multivalent systems. Ion mobility depends strongly on the glass transition temperature of the polymer electrolyte, and thus it is important to understand how Tg changes with polymer identity and ion identity and concentration.…”
Section: Articlementioning
confidence: 99%
“…[ 33,36,37 ] Many strategies, such as adding inorganic nanoparticles, [ 38–40 ] blending, [ 41 ] copolymerization, [ 42 ] and crosslinking [ 43–45 ] have been adopted to effectively suppress the crystallization of PEO and improve the ionic conductivity of PEO‐based SPEs. Coat et al [ 46 ] reported the synthesis of poly(diethylene oxide‐alt‐oxymethylene) (P(2EO‐MO)) as a polymer matrix for SPE, which has higher T g than that of PEO in the electrolyte. They found the P(2EO‐MO)/LiTFSI electrolyte exhibits a slightly lower ionic conductivity due to higher T g , but much higher Li ion transference number can be obtained in P(2EO‐MO)/LiTFSI electrolyte (0.36) than that in PEO/LiTFSI (0.19).…”
Section: Figurementioning
confidence: 99%
“…Moreover, polyether‐based electrolytes show high ionic conductivities . The introduction of highly polar chains in conjugated polythiophene derivatives can effectively enhance the ionic sensitivity .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, polyether-based electrolytes show high ionic conductivities. [23][24][25][26][27] The introduction of highly polar chains in conjugated polythiophene derivatives can effectively enhance the ionic sensitivity. [28][29][30][31][32][33][34][35][36] Many attempts have been paid on polythiophene, [31][32][33][34][35] and 3,4-alkylenedioxythiophene (XDOT)based ECPs.…”
Section: Introductionmentioning
confidence: 99%